Use of active methodologies in nursing teaching during the pandemic by COVID-19: an integrative review (Research, Society and Development, 2022)
The aim of this article is to investigate what has been produced about Active Methodologies in times of pandemic, in the context of Nursing education, through an integrative literature review. Methodology: this is a qualitative study, with a descriptive and retrospective approach, carried out through an integrative literature review, a study with data collection carried out from secondary sources, in the period of June 2021. Results: using the Virtual Health Library (VHL) 05 were selected to compose the sample of this study. Therefore, we highlight that 3 were studies in Portuguese and 2 in English. The period of publication between 2020 and 2021. Discussion: after analyzing the articles, two categories emerged to better present the content. These are: Use of active methodologies, teaching strategies and technologies in the context of a pandemic; and Challenges and obstacles of the remote modality for teaching Nursing during the pandemic. Conclusion: it is notorious that the theme is a growing one among the academic world, as it involves students and teachers, who are fundamental parts for the application and improvement of the methodology to be used in the virtual classroom.